Prompts to increase physical activity at points-of-choice between stairs and escalators: what about escalator climbers?. Issue 4 (7th August 2018) - Bellettiere, John; Nguyen, Ben; Liles, Sandy; Berardi, Vincent; Adams, Marc A; Dempsey, Paddy; Benporat, Yael; Kerr, Jacqueline; LaCroix, Andrea Z; Hovell, Melbourne
Abstract : Studies to increase physical activity at points-of-choice between stairs and escalators have historically not considered the physical activity of escalator climbing, which could influence results. Abstract: Since 1980, many studies have evaluated whether stair-use prompts increased physical activity by quantifying changes in stair use. To more completely evaluate changes in physical activity, this study addressed the often-overlooked assessment of climbing up escalators by evaluating the degree to which stair-use sign prompts increased active ascent—defined as stair use or escalator climbing. Over 5 months, at an airport stairs/escalator point of choice, we video-recorded passersby ( N = 13, 544) who ascended either stairs or escalators, on 10 days with signs and 10 days without signs. Ascenders using the stairs, standing on the escalator, and climbing the escalator were compared on days with versus without signs using multivariable logistic regression. The percentage of ascenders on days with versus without signs were as follows: stair use, 6.9 versus 3.6 percent; escalator standing, 75.2 versus 76.0 percent; and escalator climbing, 18.5 versus 20.4 percent. Signs more than doubled the odds of stair use (vs. escalator use; OR = 2.25; 95% CI = 1.90–2.68; p < .001). Signs decreased the odds of escalator climbing (vs. escalator standing or stair use); OR = 0.90; 95% CI = 0.82−0.99; p = .028). Signs increased the odds of active ascent versus escalator standing by 15 percent (OR = 1.15; 95% CI = 1.05–1.25; p = .002). Although stair-use prompts increased stair use more than twofold (125%), they increased active ascent by only 15 percent, partly because escalator climbing—a behavior not targeted by the intervention—decreased. Although our results corroborated the established consensus that point-of-choice prompts increase stair use, future studies should test interventions designed to increase active ascent.